Analysis of the Financial Feasibility of Potential Post-Pandemic Businesses Using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) Methods (Case Study: MSME Environmentally Friendly Bioplastic Products) - Tri Sunan Agung; Belinda Safa Salsabila Zuhri (PT FORMOSA CENDEKIA GLOBAL, 2023)
MSMEs play a strategic role as a driver of post-pandemic economic growth. MSME bioplastic products have the potential to contribute to economic growth and environmental sustainability. This study aims to determine the financial feasibility of MSME bioplastic products based on NPV, IRR, and PP values. The method uses evaluative research types with data processing and financial data analysis. Research shows the results of initial calculations such as 1) Investment costs of IDR 5,567,000; 2) Projected net cash flow of IDR 4,887,936 per year; 3) Determination of a discount of 6%. Based on these calculations, the results obtained are an NPV value of IDR 15,022,764.59, an IRR value of 84%, and a PP value in the 2nd year of production. Based on these three analyses, it can be concluded that the business potential of post-pandemic MSME bioplastic products can be said to be financially feasible